Light Vehicle Energy Management System using Multi-Power Sources - Hannan, MA; Azidin, FA; Mohamed, A (2012)

(untitled)
This paper describes the modelling of the energy management system (EMS) of light vehicles using hybrid multi-power source systems. The hybrid system included a fuel cell (FC), a battery, super-capacitors (SC) and a photovoltaic cell. The battery was used as the primary power source for driving the vehicle. Other sources were used as supplemental power sources for medium range vehicle usage. The control algorithm was developed as a switching mechanism used to trigger between the energy sources based on the drive of the vehicle power system as a means of examining the electrical power flow. The control algorithm was used to manage the switching operation of power supplies for the EMS during light vehicle operation. The results showed that the models were operating efficiently based on the switching control algorithm and management of the energies from various sources.